2004
DOI: 10.1021/jm0311238
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Metal Complexes of Biogenic Polyamines:  Polynuclear Platinum(II) Chelates

Abstract: Several polynuclear Pt(II) chelates with biogenic polyamines were synthesized and screened for their potential antiproliferative and cytotoxic activity in different human cancer cell lines. To gather information regarding the structure-activity relationships underlying their biological activity, the complexes studied were designed to differ in geometrical parameters such as the nature of the ligand and the number and chemical environment of the metal centers. Distinct effects were found for different cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 40 publications
(77 reference statements)
4
40
0
1
Order By: Relevance
“…In this manuscript, we describe the cytotoxic effects towards a human cancer cell line (HSC-3) of the dinuclear Pd(II) spermine (sp) chelate (PdCl 2 ) 2 (sp) (Fig. (1)) and compare it to that previously reported by the authors for the analogous Pt(II) chelate [12]. The results obtained confirm and extend those previously obtained with another polynuclear cis-dichloro(chelating diamine) system [13], i.e., an increase in cytotoxic activity upon substitution of Pt(II) with Pd(II).…”
Section: Introductionmentioning
confidence: 90%
“…In this manuscript, we describe the cytotoxic effects towards a human cancer cell line (HSC-3) of the dinuclear Pd(II) spermine (sp) chelate (PdCl 2 ) 2 (sp) (Fig. (1)) and compare it to that previously reported by the authors for the analogous Pt(II) chelate [12]. The results obtained confirm and extend those previously obtained with another polynuclear cis-dichloro(chelating diamine) system [13], i.e., an increase in cytotoxic activity upon substitution of Pt(II) with Pd(II).…”
Section: Introductionmentioning
confidence: 90%
“…The detailed knowledge of the molecular basis of the cDDP-guanine/adenine and cDDPglutathione interplay gathered in this work will pave the way for future studies on other platinum and palladium-based agents previously characterized by the authors and assessed as to their cytotoxicity towards several human cancer cell lines. [29][30][31][32][33][34][35][36][37] This will provide valuable clues for the rational design of novel cisplatin-like drugs, displaying a higher efficiency, lower toxicity, decreased acquired resistance and possible oral administration. …”
Section: Introductionmentioning
confidence: 99%
“…[6,15,17,18] In addition, it was verified that linkage of some of these molecules to previously tested anticancer drugs leads to a higher cytotoxic effect and, in some cases, even to an enhancement of the efficacy of the long-used first-generation drug cisplatin [cis-diamine dichloroplatinum(II)]. [19][20][21][22][23][24][25][26][27] Recently, it was also demonstrated that polyamines may exert insulinlike activity by interacting with receptors on fat-cell membranes. [28] Despite the vital role of polyamines in living cells, little is known about their structure at a molecular level.…”
Section: Introductionmentioning
confidence: 99%